The features of the collective modes in aerogels filled with superfluid helium - Zadorozhko, A.A.; Chagovets, V.K.; Rudavskii, E.Ya.; Sheshin, G.A.; Kekutia, Sh.E.; Chkhaidze, N.D.; Mulders, N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
The velocity of fast and slow collective modes of 90, 94 and 98% porosity aerogels filled with superfluid helium were measured by means of low-frequency resonant technique at temperatures 0.5–2.5 K. The temperature dependences of velocities of both modes are compared with the hydrodynamic theory which was modified taking into account the mobility of the aerogel matrix, porosity of media and tortuosity of an acoustic way. It has been found that the fast and slow modes in an aerogel are coupled much stronger than the first and second sounds in bulk He II.